A universal configurational entropy metric for high-entropy materials. (August 2021) - Dippo, Olivia F.; Vecchio, Kenneth S.
Abstract: In recent years, high-entropy materials have become increasingly complex, outgrowing simple solid-solution based calculations of configurational entropy, and with that, the previously established metrics for high-, medium-, and low-entropy. Those previous metrics are derived from metals-specific approximations of the entropy of fusion and the internal energy of a monatomic gas, and thus, do not apply to other materials. A new entropy metric is proposed that is universally applicable for crystalline materials, from simple solid-solution high-entropy alloys to high-entropy materials with complex crystal structures and multiple sublattices. Additionally, the methods for calculating configurational entropy in complex crystal structures are discussed. Graphical abstract: Image, graphical abstract